Development of Licorice Flavonoids Loaded Microemulsion for Transdermal Delivery Using CCD-Optimal Experimental Approach: Formulation Development and Characterization - Xin, Yang; Yun, Shi; Yuhe, Lu; Yinxue, Mao; Shurui, Niu; Yue, Zhou; Kunming, Qin; Weidong, Li (Frontiers in Nanotechnology, 2021)
In this research, we sought to surmount the poor dissolvability and transdermal absorption rate of licorice flavonoids (LFs) by fabricating a LFs microemulsion. LFs content was determined using high performance liquid chromatography. Initial studies such as dissolution testing, emulsification testing, and pseudo ternary phase diagram generation were implemented for screening components and optimized adopting the central composite design. While the tested responses were solubility, droplet size and PDI, thirteen trials were performed using two different variables, oil percentage and optimized emulsifier and co-emulsifier ratio. Microemulsions were then characterized for droplet size, PDI, transmission electron microscopy, viscosity, electrical conductivity, pH, entrapment efficiency, drug content and stability. Additionally, skin release profile, percutaneous absorption and retention were investigated adopting Franz diffusion cell. The optimal formulation was found to compose of laureth-9 (emulsifier, 6.72 g), propylene glycol (co-emulsifier, 1.80 g), isopropyl myristate (IPM, oil, 1.48 g), LFs (1.50 g) and at least more than 85% deionized water. The optimized and storage for 3 months of microemulsion was found to clear, light yellow color without phase separation or precipitation indicated the stability of the preparation to long-term placement. The mean droplet size, PDI, entrapment efficiency and drug content were discovered as 12.68 ± 0.12 nm, 0.049 ± 0.005, 97.28 ± 0.13% and 122.67 ± 0.40 mg·g−1, respectively. Furthermore, the optimal formulation sustained release LFs, remarkably deliver more LFs through the skin layer (644.95 ± 6.73 μg cm−2) and significantly retained LFs in the skin layer (9.98 μg cm−2). The study concluded that optimized microemulsion has potential and enhanced the dissolvability and cumulative penetration amount of LFs.